2018
DOI: 10.2139/ssrn.3155657
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Subventricular Zone Neural Stem Cells Release Extracellular Vesicles that Act as a Microglial Morphogen

Abstract: Highlights d Neonatal SVZ neural stem cells release extracellular vesicles d SVZ neural stem cell extracellular vesicles are targeted to microglia d Neural stem cell extracellular vesicles and RNA content regulate microglia morphology

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 65 publications
2
15
0
Order By: Relevance
“…However, it has not been clarified whether NPC‐derived EVs or exosomes influence microglia in CNS disorders. In the present study, we found that grafted exosomes recruited microglia to the site of injection and activated microglia, which presented as a rounded shape that was consistent with that reported by Morton et al [35]. Interestingly, Morton et al observed rounded microglia up to day 7, while we found that the rounded microglia returned to ramified shape at day 7 post‐injection of mNPC‐exos (48 hours incubation of exosomes in vitro ), and the density of microglia in the ONL and SRS decreased in our model.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…However, it has not been clarified whether NPC‐derived EVs or exosomes influence microglia in CNS disorders. In the present study, we found that grafted exosomes recruited microglia to the site of injection and activated microglia, which presented as a rounded shape that was consistent with that reported by Morton et al [35]. Interestingly, Morton et al observed rounded microglia up to day 7, while we found that the rounded microglia returned to ramified shape at day 7 post‐injection of mNPC‐exos (48 hours incubation of exosomes in vitro ), and the density of microglia in the ONL and SRS decreased in our model.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have reported that NPC‐EVs were taken up by microglia and regulated microglial morphology and function during brain development [35]. It has also been reported that microglial activation and associated inflammatory responses impact the progression of RD [54,55].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite this, the biological response of MC to CPP transfer of fibroblast cytoplasm in our separate work (1,18,34), seems more similar to the published response of cells to uptake of exosomes, than to TNT mediated transfer. For example, exosome uptake alters cell morphology (14,15,42), but we find no literature of TNT mediating this effect. Similarly, while exosomes from a variety of sources can increase migration of several cell types (16,(43)(44)(45)(46), there is less evidence for a similar effect for cellular contents transferred via TNT (17).…”
Section: Discussionmentioning
confidence: 68%
“…As major immune-competent cells in the brain, microglia exert multiple functions under various physiological and pathological conditions (Wolf, Boddeke, & Kettenmann, 2017). Notably, recent studies have demonstrated that microglia regulate proliferation and differentiation of NSCs and OPCs either positively or negatively depending on conditions, thereby affecting the cellular dynamics of the postnatal brain in both the VZ-SVZ and DG (Kreisel, Wolf, Keshet, & Licht, 2018;Morton, Neckles, Seluzicki, Holmberg, & Feliciano, 2018;Naruse, Shibasaki, Shimauchi-Ohtaki, & Ishizaki, 2018;Vay et al, 2018;Walton et al, 2006). Yet, what impact microglia have on normal brain development remains to be further investigated.…”
Section: Box 1 Impacts Of Non-neuronal/glial Cell Types On Postnatal mentioning
confidence: 99%